Penerapan Six Sigma Upaya Peningkatan Produktivitas Pada Perusahaan Moulding Plastik (Studi Kasus PT. Mega Teknology Batam) - Decky Antony Kifta; Ilhamyah Sipahutar (Prosiding, 2018)
One of the biggest problem which may hinder the company to improve its productivity is quality problem. Productivity can be increased if the product is in good quality or free of defect. PT Mega Technology Batam, is a company which produce Cover Coffee Maker (CCM) is also facing the same problem. The Company found that the rejected quantities reached up to 197,464 pieces. This will give reject rate percentage up to 5.99% from the total quantities produced within a month. The baseline performance was calculated to DPMO (Defects per Million Opportunity) and gave the figure of 59,929.39 or which is equal to Sigma Level 3.1. The rejected items quantities are big, reject rate percetange is high and Sigma Level is low. In order to find all the answers, the researcher used all methods of Seven Tools such as Check Sheet, Cause-Effect Diagram (Fishbone), Histogram, Pareto Diagram, Run Chart, Control Chart and Scattered Diagram. It was found that Company performed less training to its workers.and in order to resolve these issues or problems, therefore, corrective actions were implemented using 5W-1H technique, and after the actions implemented the researcher then found that the Sigma level is improved to the point of 3.7.